“Highly Read and Poorly Cited?” A Critical Perspective on Academic Social Networks - Pagliaro, Mario (Journal of Data Science, Informetrics, and Citation Studies)
On the occasion of 300,000 reads of our team’s studies archived on ResearchGate, an Academic Social Network (ASN), this study offers a critical perspective on academic social networks from the perspective of research and educational dimensions of scholarly work. Findings of previous studies for which poor correlation between reads of articles archived in ASNs and citations exists are confirmed by this investigation. Academic social networking, however, provides unique benefits that deserve to be clearly identified to fulfil the potential of these digital resources available since 2009.
Keywords: Open science; Citations; ResearchGate; Research impact; Academic social network.